Irish nationalism and European integration the official redefinition of the island of Ireland - Hayward, Katy (Manchester Univ. Press, 2009)
This study provides an analysis of the EU/nation-state relationship, including compelling evidence that nationalism and European integration are complementary (rather than competing) processes. It also reveals the conceptual changes made by Irish politicians in order to justify major about-turns in ideology and policy on Irish unity.